A new pyrrolidinedithiocarbamate screening method for the determination of methylmercury and inorganic mercury relation in hair samples by HPLC-UV-PCO-CVAAS - Falter, Ralf; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1996)
A new analytical screening technique for the determination of methylmercury and inorganic mercury in hair samples by HPLC-PCO-CVAAS has been developed. It is based on the extraction of mercury compounds by a buffered sodium pyrrolidinedithiocarbamate solution, separation by reversed-phase HPLC, post column oxidation by UV-irradiation, reduction with alkaline sodium borohydride, and determination by cold vapour atomic absorption detection. The standard deviation was 7% and recoveries were 90% for both compounds. The limit of detection (S/N = 3) for both compounds was calculated to be about 4 ppb.